Impact load-induced microstructural damage of concrete made with unconventional aggregates - Erdem, Savas (2012)
Understanding the correlation between the mix proportions, micro structural characteristics, and macro-scale properties of concrete (i.e. the process-structure-properties relationship) is fundamental to achieving a more advanced understanding of how to apply and optimise this abundant engineering material. Although, concrete has been traditionally evaluated by its physico-mechanical and functional properties; development of advanced and effective inspection techniques during the last decade has demonstrated that fundamental macro-level properties of concrete depend, to a great extent, on its properties at the micro- and nano levels. This research was intended to make a quantitative assessment of impact load-induced micro-structural damage in concrete and, more particularly, to investigate the influence of ITZ micro-and nano local properties (as influenced by aggregate characteristics) on the impact load-induced cracking behaviour of concrete.